Vertical Fiscal Externalities and the Environment - Christoph Böhringer; Nicholas Rivers; Hidemichi Yonezawa (Center for Economic Studies and ifo Institute (CESifo), 2014)
We show that imposition of a state-level environmental tax in a federation crowds out preexisting federal taxes. We explain how this vertical fiscal externality can lead unilateral state-level environmental policy to generate a welfare gain in the implementing state, at the expense of other states. Using a computable general equilibrium model of the Canadian federation, we show that vertical fiscal externalities can be the major determinant of the welfare change following environmental policy implementation by a state government. Our numerical simulations indicate that - as a consequence of vertical fiscal externalities - state governments can reduce greenhouse gas emissions by over 20 percent without any net cost to themselves.
Keywords: C68; H70; Q40; 330; fiscal externality; climate policy; federalism; computable general equilibrium